CUSTOMER PERCEPTIONS OF SERVICE QUALITY AT MARIZA DEPARTMENT STORE IN MADIUN REGENCY - Prihatinta, Triana; Tri Hastuti, Farida; Wisniandita Putri, Dinda (Epicheirisi: Jurnal Manajemen, Administrasi, Pemasaran dan Kesekretariatan, 2025)
This study aims to analyze and describe customer perceptions of service quality at Mariza Department Store, with the findings expected to serve as evaluation material for improving service quality. The assessment of service quality was carried out using the five Servqual dimensions: reliability, responsiveness, assurance, empathy, and tangibles. The research employed a quantitative descriptive method, with numerical data presented in descriptive form. Data were collected from 75 respondents through a questionnaire as the primary instrument. The data analysis process involved data tabulation, classification based on Servqual dimensions, calculation of mean scores for each indicator, and interpretation using descriptive statistics to provide an objective picture of customer perceptions. The results revealed that overall, the service quality at Mariza Department Store in Madiun Regency was considered fairly good, with a score of 64%. Meanwhile, the evaluation of each service quality indicator showed 44% for reliability, 68% for responsiveness, 51% for assurance, 64% for empathy, and 63% for tangibles.